Efficacy of attractants in controlling the corn maggot (Euxesta spp.) and their impact on corn yield (Agroindustrial Science, 2025)
The amylaceous maize (Zea mays L.), specifically the Blanco Urubamba PMV 560 variety, is a strategic crop for the food security and economy of high Andean communities in Peru. However, its production is threatened by the corn silk fly (Euxesta spp.), a pest that significantly reduces both yield and grain quality. This study evaluated the effectiveness of four attractants and a control, applied through McPhail traps, in reducing Euxesta spp. populations in maize fields in the Apurímac region, Peru. The number of captured adult flies (ECM), number of larvae per ear (NLM), incidence of ear damage (IDM), and grain yield (RGH) were assessed. The treatment using hydrolyzed protein (T5) recorded 691,5 ± 105,6 ECM, 44.6 ± 5,0 NLM, and 11,7 ± 1,6 IDM, showing statistically significant differences (p < 0,01) compared to the control treatment (T1), which recorded 1,2 ± 0,4 ECM, 82 ± 4,3 NLM, and 38,3 ± 0,9 IDM. In terms of yield, T5 achieved 3,22 ± 0,4 t/ha, while T1 yielded only 1,06 ± 0,1 t/ha. The results suggest that hydrolyzed protein is an effective option for reducing Euxesta spp. pressure and enhancing maize productivity in high-altitude Andean regions.
Keywords: starchy maize; attractant baits; McPhail traps; Euxesta spp.; integrated pest management; sustainable agriculture